ТАРЖИМАДА ПРАГМАТИК МУАММОЛАР ҲАМДА ТАРЖИМА ПРАГМАТИКАСИНИНГ ЎЗИГА ХОС ХУСУСИЯТЛАРИ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
According to the study of semiotic signs, each sign, including the signs in language, must be seen from three sides: syntax, that is, the relationship between signs; semantics, that is, the relationship between the sign and the actual situation; and pragmatics, which is the relationship between a sign and its users. This article discusses the concept of pragmatics and pragmatic problems of translation.
Keywords: pragmatics, syntax, semiotics, sign system, translation, semantics.